"Hand-it-on": an innovative simulation on the relation of non-technical skills to healthcare. Issue 1 (January 2016) - Dieckmann, Peter; Zeltner, Louise; Helsø, Anne-Mette
Abstract Non-technical skills (NTS) are an integral part of the abilities healthcare professionals need to optimally care for patients. Integrating NTS into the already complex tasks of healthcare can be a challenge for clinicians. Integrating NTS into simulation-based training increases the demands for simulation instructors with regard to scenario design, conduct, and debriefing. We introduce a simulation game, Hand-it-on, that can trigger discussions on how NTS can influence work processes.Hand-it-on aims to help clinicians and simulation instructors alike to improve their understanding of NTS concepts and where they can apply them in their work. It complements existing approaches to teaching NTS by limiting the complexity of the game and by removing medical content, allowing learners to concentrate on NTS.Hand-it-on is relevant for groups and teams working across the range of different healthcare contexts. DuringHand-it-on, participants stand in a circle and hand on everyday objects to each other according to simple rules, resulting in many events that can be debriefed in relation to safe patient care. We describe both the conduct ofHand-it-on and ideas on how to debrief participants. We provide variations that can be used in different contexts, focusing the exercise on different learning goals. We also offer the theoretical rationale for using an out-of-context simulation in combination with other forms of teaching. Although we did not evaluateHand-it-on formally, oral feedback from participants and the replication ofHand-it-on by many simulation teams support its value.